2006
DOI: 10.1111/j.1834-7819.2006.tb00422.x
|View full text |Cite
|
Sign up to set email alerts
|

The pH change after HCl titration into resting and stimulated saliva for a buffering capacity test

Abstract: Background: Saliva collection can provide clinical information about individual patients. However, a correlation between ranking buffering capacity using resting and stimulated saliva is still unknown. The aim of this study was to evaluate the pH change after HCl titration into resting and stimulated saliva for a salivary buffering capacity test. Methods: Resting and stimulated saliva (by chewing paraffin wax) were collected from 80 patients. After the pH of both saliva samples was measured using a hand-held p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 22 publications
(28 reference statements)
1
36
0
2
Order By: Relevance
“…[4,5] The major regulator of pH is salivary bicarbonate from parotid saliva. [6] The mean or average pH of normal resting saliva is 6.75, which shows that normal resting saliva is slightly acidic. [5,7] Hawkins [8] reported that there was a higher pH in saliva of persons who are immune from caries than in those who are susceptible.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The major regulator of pH is salivary bicarbonate from parotid saliva. [6] The mean or average pH of normal resting saliva is 6.75, which shows that normal resting saliva is slightly acidic. [5,7] Hawkins [8] reported that there was a higher pH in saliva of persons who are immune from caries than in those who are susceptible.…”
Section: Introductionmentioning
confidence: 99%
“…Literature values are reported in different ways. Some research groups have simply quoted the buffer capacity to be high, medium or low, without providing any actual value [27]. Thus one cannot draw direct comparisons between studies.…”
Section: Introductionmentioning
confidence: 99%
“…The saliva of fixed orthodontic appliances patients had lower pH, buffering capacity and calcium concentration than that of patients without it. These oral changes are enough to cause tooth demineralization [23]. The saliva buffering capacity, defined as salivary resistance to change in pH, is assigned to carbonate bicarbonate systems, phosphates and proteins [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Mixture was vigorously shaken. Then stream of Nitrogen was passed through the mixture for 20 minutes to eliminate carbon dioxide from the sample and allowed to stand for 10 min when the final pH is measured [23].…”
Section: Salivary Ph and Buffering Capacitymentioning
confidence: 99%